A CMOS Compatible Ultracompact Silicon Photonic Optical Add-Drop Multiplexer with Misaligned Sidewall Bragg Gratings - Md Ghulam Saber; Zhenping Xing; David Patel; Eslam El-Fiky; Nicolas Abadia; Yun Wang; Maxime Jacques; M. Morsy-Osman; David V. Plant (IEEE Photonics Journal)
We experimentally and via simulations demonstrate ultracompact single-stage and cascaded optical add-drop multiplexers using misaligned sidewall Bragg grating in a Mach–Zehnder interferometer for the silicon-on-insulator platform. The single-stage configuration has a device footprint of 400 ${μ }\text{m}\,×$ 90 ${μ }\text{m}$ , and the cascaded configuration has a footprint of 400 ${μ }\text{m}\,×$ 125 ${μ }\text{m}$ . The proposed designs have 3-dB bandwidths of 6 nm and extinction ratios of 25 dB and 51 dB, respectively, and have been fabricated for the transverse electric mode. A minimum lithographic feature size of 80 nm is used in our design, which is within the limitation of 193 nm deep ultraviolet lithography.